Pemberdayaan Komunitas Belajar Guru Dalam Mengimplementasikan Pembelajaran Berdiferensiasi - Supriyadi Supriyadi; Dina Maulina; Irwandani Irwandani; Marlina Kamelia (Jurnal Pemberdayaan Masyarakat, 2024)
Differentiated instruction has been a focus among educators since the emergence of the Merdeka Curriculum. This approach is recognized as a fundamental strategy in facilitating student-centered learning by aligning instructional methods with their diverse learning needs. However, teachers in schools with limited resources still encounter challenges in effectively implementing differential learning. Therefore, this community empowerment initiative aims to enhancing the teaching community in school mover to design and implement differential learning effectively. The Asset Based Community Development (ABCD) approach serves as the guiding framework for this empowerment, facilitating teacher training in the design, implementation, and evaluation of differential learning strategies. This initiative is manifested through various collaborative activities, including workshops, group discussions, share best practices, and collective reflection within the school's teaching community. The result of this empowerment initiative demonstrate that collaborative approach can significantly enhance teacher competence in developing and implementing differentiated instruction. Therefore, this empowerment model holds the potential for broader adoption within other educational communities, thereby extending its positive impact on enhancing the quality of learning processes.